Experiences of general practitioner continuity among women with chronic fatigue syndrome/myalgic encephalomyelitis: a cross-sectional study. Issue 1 (December 2016) - Hansen, Anne; Lian, Olaug
Abstract Background Continuity of care is important for patients with chronic illness in need of coordinated healthcare services from multiple providers. Little is known about how patients with chronic fatigue syndrome/myalgic encephalomyelitis (CFS/ME) experience continuity of GP care. This study explores how women with CFS/ME experience GP care across the three dimensions of continuity: informational, management, and relational continuity. Methods This cross-sectional study uses questionnaire data collected from members of The Norwegian ME Association. Descriptive statistics and logistic regressions were used to estimate experiences of continuity, and associations with age, education, self-rated degree of CFS/ME, duration of the GP relation (GP duration), and number of GP visits for CFS/ME-related issues during the previous year (GP frequency). Results Almost two-thirds of participants reported positive experiences across all three dimensions of GP continuity of care; 64.4% for informational, 64.1% for management, and 77.2% for relational continuity. Lower educational attainment was associated with more negative experiences of informational continuity (primary school only compared to university educated: odds ratio [OR] 0.12, confidence interval [CI] 0.03–0.49, p = 0.003). Compared to participants aged 40–59 years, those aged 60+ years were significantly less likely to have experienced poor (negative) management continuity (OR 0.25, CI 0.09–0.76, p = 0.014). A GP relationship of three or more years was associated with positive experiences of relational continuity (OR 2.32, CI 1.09–4.95, p = 0.030). Compared to those with moderate CFS/ME, those who graded their CFS/ME as severe or very severe were significantly more likely to have negative experiences of relational continuity (OR 0.38, CI 0.14–0.99, p = 0.047). Conclusions A large proportion of participants experienced all three aspects of continuity of GP care (especially the relational dimension) positively. Informational and management continuity scores were moderately lower. Our results suggest greater emphasis on information giving, feedback, and better coordination of care to be good strategies for practice improvement for this patient group.